Entwicklung von Bestellerentgelten im Busverkehr. Analyse des Ausschreibungswettbewerbs im RMV, MVV und HVV. - Beck, Arne; Wanner, Karen (Deutscher Verkehrs-Verl., 2008)
Die Verkehrsverbünde Rhein-Main-Verkehrsverbund (RMV), Münchner Verkehrs- und Tarifverbund (MVV) und Hamburger Verkehrsverbund (HVV) führten seit 1996 eine Vielzahl von Ausschreibungsverfahren für Busverkehrsdienstleistungen durch. Ziel war es, die Effizienz des Gesamtsystems ÖPNV zu steigern. Unter der Prämisse, die Qualität im Busverkehr zu sichern bzw. zu steigern sowie die Chancen des Mittelstands und der Chancen der Beschäftigten zu sichern, sollten die Kosten aus Sicht der Aufgabenträger in der Gesamtbetrachtung dauerhaft gesenkt werden.

Since 1996, the German public transport associations ("Verkehrsverbünde" RMV MVV and HVV have been tendering a significant number of bus routes. The study 'Der Busverkehr im Wettbewerb' (Competition within public transport by bus) showed that Public Transport Authorities could reduce their franchise payments considerably as a result of tendering. Furthermore, the price level has been stable for the last ten years and the degree of competition has been high. The price dispersion tends to decline with an increasing scope of service of the route bundles. Starting from a lot size of one million vehicle-kilometre, prices range between 1,59 Euro and 1,85 Euro. In accordance to secure the level of franchise payments from a PTA's point of view, it is recommended to keep down market entry barriers, to avoid price fixing (cartel agreements) and to design the terms of tender calculable to prevent misallocations for the participating companies.
Development of orderer-fees in the bus traffic.
Keywords: Öffentlicher Verkehr; Busverkehr; ÖPNV; Ausschreibung; Kostensenkung; Verkehrsunternehmen; Verkehrsverbund; Wettbewerb; Vergabeverfahren; Verkehrsdienstleistung; Aufgabenträger; Evaluation